Cox regression and survival analysis from the tauro-urso-deoxycholic trial in amyotrophic lateral sclerosis - Reggiardo, Giorgio; Lo Giudice, Maria; Lalli, Stefania; Rinaldi, Gilberto; Albanese, Alberto (Frontiers in Neurology, 2023)
Recent phase II pilot clinical trials suggested that tauro-urso-deoxycholic acid (TUDCA) might slow functional decline and increase survival in patients with amyotrophic lateral sclerosis (ALS). We performed a multivariate analysis of the original TUDCA cohort to better define the treatment effect and allow comparability with other trials. Linear regression slope analysis showed statistical differences in the decline rate, favoring the active treatment arm (p-value < 0.01; −0.262 for the TUDCA group and −0.388 for the placebo group). Mean survival time, estimated by the Kaplan–Meier analysis, showed a 1-month difference, favoring active treatment (log-rank test p-value = 0.092). Cox regression analysis demonstrated that placebo treatment was associated with a higher risk of death (p-value = 0.055). These data further support the disease-modifying effect of TUDCA monotherapy and raise the question of what could be the additional effect of combining TUDCA with sodium phenylbutyrate.